Policy Analysis In Improving The Resilience Of The Karo Community: A Comparative Study Before And After The Eruption Of Mount Sinabung - Agung, Muhammad Sutan; Hariani, Riri Rezeki; Srikusuma, M. Rohmidhi; Harve, Renhard (Universitas Syiah Kuala, 2025)
This research aims to analyze the policies implemented in an effort to improve the resilience of the Karo community to the Mount Sinabung eruption disaster, with a comparative study approach between conditions before and after the eruption. The recurrent eruption of Mount Sinabung since 2010 has had a significant impact on the social, economic and environmental aspects of the surrounding community. Social resilience is an important factor in dealing with and recovering from the disaster. Through qualitative methods with primary and secondary data collection, this study evaluates the effectiveness of disaster mitigation and adaptation policies implemented by local governments and related institutions. The results show that policies that integrate local wisdom and active community participation significantly improve the adaptive capacity and social resilience of the Karo community post-eruption. The study also identifies constraints and opportunities in policy implementation, which can be used as recommendations for improving disaster mitigation policies in the future. The findings of this study reinforce the importance of community-based policy approaches and local wisdom in building the resilience of disaster-prone communities.